PSYCHOLOGICAL-PEDAGOGICAL FACTORS OF FORMING LEARNING MOTIVATION IN PRIMARY SCHOOL (Universal International Scientific Journal, 2026)
This article analyzes the psychological and pedagogical factors of the formation oflearning motivation in primary school students. The essence of learning motivation, its role in thedevelopment of children of primary school age and its importance in the educational process arehighlighted. The role of the teacher's pedagogical skills, teaching methods, positive psychologicalenvironment and encouragement in increasing students' interest in learning is also considered. Thearticle substantiates effective pedagogical approaches that serve to form stable learning motivationin primary school students, as well as psychological conditions.
Keywords: Ability; learning motivation; primary school age